Pengaruh Pemanfaatan Teknologi Informasi, Perpustakaan Dan Lingkungan Kampus Terhadap Prestasi Belajar Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Islam Malang - Hamzah Ahmad Rabbani; Muhammad Mansur; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study aims to determine and analyze the effect of the use of information technology, libraries, and the campus environment on student achievement of the Faculty of Economics and Business, Islamic University of Malang. The type of approach used is explanatory research. The sample used in this study uses the Malhotra formula, the number of indicators is multiplied by 5, 16 x 5 = 80. The data analysis method used in this study is multiple linear regression analysis. Testing the data used is testing the simultaneous hypothesis (Test F) and testing the partial hypothesis (Test t). The results of his research indicated that the use of information technology, libraries and the campus environment had a positive and significant influence simultaneously on student achievement of students of the Faculty of Economics and Business, Islamic University of Malang. Utilization of information technology has a positive and significant effect on student achievement of the Faculty of Economics and Business, Islamic University of Malang. Libraries have a positive and significant effect on student achievement of the Faculty of Economics and Business, Islamic University of Malang. The campus environment has a positive and insignificant effect on student achievement of the Faculty of Economics and Business, Islamic University of Malang. Keywords: Utilization Information Technology, Libraries and Campus Environment